1996
DOI: 10.1002/(sici)1098-240x(199608)19:4<331::aid-nur7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The nursing practice environment, staff retention, and quality of care

Abstract: The effects of key factors in the nursing practice environment--management style, group cohesion, job stress, organizational job satisfaction, and professional job satisfaction--on staff nurse retention and process aspects of quality of care were examined. Hinshaw and Atwood's (1985) anticipated turnover model was modified and expanded to include relevant antecedent and outcome variables. The four-stage theoretical model was tested using data from 50 nursing units at four acute care hospitals in the southeast.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(121 citation statements)
references
References 0 publications
3
109
0
4
Order By: Relevance
“…This result is not unique to South Africa as evidence shows that health system reforms in the Africa region [76] or elsewhere [77] tend to expand or extend the roles of health workers, but are often imposed on health workers without their inputs or with insufficient discussion, thereby affecting job satisfaction and/or health service delivery. Existing evidence suggests that shared governance and leadership and health worker inclusion in the development of policies and strategies is an important aspect that positively influences job satisfaction and retention of nursing managers [78]. …”
Section: Discussionmentioning
confidence: 99%
“…This result is not unique to South Africa as evidence shows that health system reforms in the Africa region [76] or elsewhere [77] tend to expand or extend the roles of health workers, but are often imposed on health workers without their inputs or with insufficient discussion, thereby affecting job satisfaction and/or health service delivery. Existing evidence suggests that shared governance and leadership and health worker inclusion in the development of policies and strategies is an important aspect that positively influences job satisfaction and retention of nursing managers [78]. …”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, this approach takes advantage of the daily cost-effective and quality-of-care benefits of adequate nurse staffing (Rothberg, Abraham, Lindenauer, & Rose, 2005). The call for hospitals to act has been in place since the Institute of Medicine’s (1983) report Nursing and Nursing Education: Public Policies and Private Actions , and the subsequent research that has demonstrated the relationships among poor staffing and poor work environments, nurse burnout, turnover, and professional attrition (Aiken, Clarke, Sloane, Lake, & Cheney, 2008; Aiken, Clarke, Sloane, Sochalski, & Silber, 2002; Leveck & Jones, 1996; Stone et al, 2007). Evidence supports programs like Magnet Hospital designation, which is given to hospitals that satisfy a set of criteria designed to measure the strength and quality of their nursing, including adequate staffing.…”
Section: Addressing Nursing Workforce Surge Capacitymentioning
confidence: 99%
“…There is indeed mounting evidence that the adverse working conditions and low satisfaction of nurses are associated with increased nursing turnover (Davidson, Folcarelli, Crawford, Duprat & Clifford, 1997;Irvine & Evans, 1995;Leveck & Jones, 1996). It is the high-risk groups that are more likely to exhibit turnover behaviour if the work environment is not perceived as positive in terms of various outcomes.…”
Section: Summary Of Findingsmentioning
confidence: 99%